2010
DOI: 10.1007/s10886-009-9738-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Ecology of the Emerald Ash Borer Agrilus planipennis

Abstract: The emerald ash borer (EAB), Agrilus planipennis Fairmaire (Coleoptera: Buprestidae) is a serious invasive pest that has caused devastating mortality of ash trees (Fraxinus sp., Oleaceae) since it was first identified in North America in 2002. Shortly after its discovery, surveys were conducted, based on the visual inspection of trees. The shortcomings of visual surveys have led to a critical research need to find an efficient survey method for detecting A. planipennis infestations. Here, we present a review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
98
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 83 publications
(142 reference statements)
0
98
1
1
Order By: Relevance
“…After the discovery of EAB in North America, initial monitoring was based on the visual signs and symptoms of infestation such as D-shaped exit holes left by the emerging adults, longitudinal cracks in the bark over the S-shaped larval galleries, canopy dieback, epicormic shoots and woodpecker damage [90]. Accurate detection and monitoring methods of EAB populations and newly established infestations have been difficult to develop, which greatly hinders the ability to effectively manage for this pest.…”
Section: Past and Present Detection Methods And Treatment Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the discovery of EAB in North America, initial monitoring was based on the visual signs and symptoms of infestation such as D-shaped exit holes left by the emerging adults, longitudinal cracks in the bark over the S-shaped larval galleries, canopy dieback, epicormic shoots and woodpecker damage [90]. Accurate detection and monitoring methods of EAB populations and newly established infestations have been difficult to develop, which greatly hinders the ability to effectively manage for this pest.…”
Section: Past and Present Detection Methods And Treatment Optionsmentioning
confidence: 99%
“…Furthermore, a long range pheromone has not yet been detected for EAB [92]. Two short range, contact pheromones produced by adult emerald ash borer females have been identified that are antennally attractive to the males and have been used to improve trap captures [80,90,93,94]. Currently, key survey methods include the use of external signs and symptoms, green and purple sticky prism traps baited with ash volatile lures, green multi-funnel traps, trap logs, and using girdled trap trees which are an expensive and destructive method [15,88,92,95].…”
Section: Past and Present Detection Methods And Treatment Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the arrival of the emerald ash borer in North America, little was known of its chemical ecology or that of its congeners (Crook & Mastro 2010). It now is understood that the emerald ash borer depends largely on volatiles and visual cues to locate hosts and uses visual cues and short-range sex pheromones to locate mates (Crook & Mastro 2010;Silk & Ryall 2015). The lack of economic importance of most native Buprestidae has precluded the need for conducting such basic chemical ecology research, and thus little is known about them.…”
mentioning
confidence: 99%